Two new species of Sundarion (Hemiptera: Membracidae: Darninae) and taxonomic notes on two congeneric taxa - Antonio J. Creão-Duarte; Albino M. Sakakibara (Zoologia (Curitiba), 2016)
ABSTRACT Two new species of Sundarion Kirkaldy, 1904 - Sundarion flavopiceum sp. nov. (from Brazil, state of Pará, Serra Norte) and Sundarion marmoratum sp. nov. (from French Guiana, Montagne des Chevaux) - are described. The first species differs from S. flavum (Fairmaire, 1846) in having smaller supra-humeral horns, and being dark brown with a large yellow spot on each side of the posterior process. In this aspect, it resembles Alcmeone picea (Fairmaire, 1846). The second species is similar to S. flavum except for being variegate yellowish-brown. Taxonomic comments are provided for S. notabile Souza & Rothéa, 2005, which was previously known only from males, and for S. compressicornis (Fairmaire, 1846) comb. nov., originally described in Hemiptycha Germar, 1833 and latter transferred to Hemikyptha Metcalf, 1927. New geographical distribution records are provided for both species.